(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to investigate the patterns of NSAIDs use, assess gastrointestinal and cardiovascular risk factors, and identify confounding factors that influence the prescription of COX-2 selective NSAIDs in musculoskeletal patients. Methods: A descriptive cross-sectional study was conducted using 220 inpatient and outpatient medical records of musculoskeletal patients who were treated at the University Medical Center Ho Chi Minh city Branch 3 from January to June 2023. Patients aged ≥ 18 years and having used at least one type of NSAID were included in the study. Data collection process involved analyzing medical records and recording demographic characteristics, comorbidities, types of NSAIDs used, duration of NSAID use, as well as gastrointestinal and cardiovascular risks. Deborah Layton risk score was applied to assess the gastrointestinal and cardiovascular risks, which were classified into three categories: low, moderate, and high. Results: The average patient age was 50.5 ± 14.9 years, with 74% of patients aged between 18 and 60 years. The most common musculoskeletal conditions were osteoarthritis and back pain, whose proportions were 58.2% and 20%, respectively. A high rate of comorbidities (81.4%) was observed, with the trào ngược dạ dày thực quản (45,5%) and dyslipidemia (30%) being the most prevalent. Meloxicam (44.1%) and Celecoxib (38.2%) were the most frequently prescribed oral NSAIDs. A total of 71.8% of patients used NSAIDs for a short duration (< 14 days), and 51.8% were co-prescribed proton pump inhibitors (PPIs). Moderate gastrointestinal and cardiovascular risks were the most prevalent, accounting for 60.5% and 57.7%, respectively. The logistic regression analysis showed that “comorbidities” (OR = 3.17; 95% CI from 1.21-8.30; p = 0.019) and “high gastrointestinal risk” (OR = 2.98; 95%CI from 1.38-6.45; p = 0.005) were significant confounding factors influencing the prescription of the COX-2 selective NSAIDs. Conclusions: The pattern of NSAIDs use in the treatment of musculoskeletal diseases prioritizes selective COX-2 inhibitors, such as meloxicam and celecoxib. “Comorbidities” and “high gastrointestinal risk” are two key factors influencing the prescription of COX-2 selective NSAIDs.